Política, economía, individualismo, globalización, feminismo, decolonialidad - García López, Ernesto (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The 15th of May of 2011 an International outraged social movement started against the political powers and especially against the economic ones. The nucleus of this social movement was the rejection against the “Budget reduction plans” boosted by the different European governments due to the economic crisis. The different western democracies seemed to submit to the interests of “the markets” against the will of most of its citizens. Why is economy controlling politics? Which are the historical and cultural characteristics that shape this relationship? Is the actual financial crisis a surprising explosion or are there enough proofs to consider that its roots exist in a concrete socio-cultural configuration? Through a revision of different authors who have reflected about these topics, I will analyse some elements that explain the autonomous working of economy and the subjection of politics to its logics, conditions and theoretical proposals.